2020
DOI: 10.1186/s12879-020-05313-y
|View full text |Cite
|
Sign up to set email alerts
|

The sputum microbiome associated with different sub-types of AECOPD in a Chinese cohort

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is one of the most prevalent diseases worldwide. Episodes of acute exacerbations of COPD (AECOPD) are associated with disease severity and progression. Although substantial progress has been made in understanding the dynamics of AECOPD, little is known about the sputum microbiome of AECOPD in the Chinese population. Methods: In this study, we characterized the sputum microbiomes from sputum specimens collected from healthy controls (n = 10), stable (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
(57 reference statements)
1
17
0
Order By: Relevance
“…Proteobacteria and its members such as Haemophilus were associated with the onset of AECOPD [ 27 ]. In the present study, the most dominant phylum in sputum samples from the stable COPD group was Firmicutes, consistent with previous findings [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…Proteobacteria and its members such as Haemophilus were associated with the onset of AECOPD [ 27 ]. In the present study, the most dominant phylum in sputum samples from the stable COPD group was Firmicutes, consistent with previous findings [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…When the stable and exacerbated states of disease were compared in this study a higher abundance of the Firmicutes phylum (2% higher in the exacerbated state) and lower abundances of the Proteobacteria (2% higher in the exacerbated state), Actinobacteria (3% higher in the exacerbated state) and Bacteroidetes phyla (2% higher in the exacerbated state) was observed. Previous studies (all conducted using sputum specimens) that have compared the two diseases states in COPD have observed the same trend, where one of the phyla shows an increased prevalence and the other phyla showed a decreased prevalence in the exacerbated state, however, none of these studies reported the percentage increase 66 71 . In most of these studies, Proteobacteria increased, however, two studies [Jubinville et al .…”
Section: Discussionmentioning
confidence: 85%
“…(2020)], showed an increased prevalence of Firmicutes (as observed in this study). These studies had a variety of different sample sizes (ranging from nine participants to 281 participants), were conducted in USA, Europe and China and used different sequencing technologies (454 sequencing, MiSeq sequencing and PhyloChip) 66 71 .…”
Section: Discussionmentioning
confidence: 99%
“…AECOPD refers the acute situation of COPD featured by the worsening of the patient's respiratory symptoms. [ 16 ] Bacterial infection is a leading reason for AECOPD, and antibiotic treatment is necessary for the patients. In addition to antibacterial treatment, the appropriate NIPPV treatment could shorten the hospitalization time, improve the pain, and reduce the need of endotracheal intubation.…”
Section: Discussionmentioning
confidence: 99%